THE EFFECT OF GAMIFICATION ON STUDENTS’ MOTIVATION TOWARD LEARNING ENGLISH - Saidgul, Sazan; Mohammed, Fakhir (Humanities Journal of University of Zakho, 2024)
The current study investigates the effect of gamification (i.e., Duolingo) on students' motivation and engagement toward learning English. Gamification incorporates game elements into non-game contexts like education to increase user engagement. By using quantitative methods for collecting the data, a questionnaire of 15 statements was utilized and distributed on 60 (12-17 years old) participants. After obtaining the data, and using Excel sheets, the results showed that most students found Duolingo easy to use for learning English. Over half felt the games were engaging and helped improve their skills, especially speaking and writing. However, some found the games ineffective or time consuming. Most students were motivated and challenged yet also needed support in using Duolingo effectively. The students preferred Duolingo over traditional methods and planned to continue using it. Generally, to know the impressions of a sample of students about using gamification for their education will be helpful for students as well as teachers to boost learning outcomes and provide more guidance on effective usage.